Systemic canine protothecosis - Souza , Liza N.; Estrela-Lima, Alessandra; Moreira, Eduardo L. T.; Ribeiro, Lorena G. R.; Xavier , Mariana N.; Silva , Teane M. A.; Costa , Érica A.; Santos, Renato L. (Brazilian Journal of Veterinary Pathology, 2009)
Protothecosis is a rare disease caused by achlorophyllic algae of the genus Prototheca. This case involved a 5 year- old intact female Cocker Spaniel, with a history of mild and persistent diarrhea that was not responsive to treatment. Clinical signs progressed to watery and bloody diarrhea followed by development of ocular signs, including complete and bilateral retinal displacement, glaucoma, synechia, and blindness. At necropsy, lesions observed consisted of necro- hemorrhagic enteritis, and multiple white nodular lesions in the heart, pancreas, kidneys, and thyroid gland. Microscopically, the nodular lesions were characterized by a chronic histiocytic inflammatory infiltrate associated with a severe accumulation of organisms with morphology and histochemical features compatible with Prototheca sp.